Ion and water transport properties of cation exchange membranes prepared by heavy-ion-track grafting technique. Issue 12 (12th August 2020) - Sawada, Shin-ichi; Goto, Mitsuaki; Koshikawa, Hiroshi; Kitamura, Akane; Higa, Mitsuru; Yamaki, Tetsuya
ABSTRACT: For high-performance electrodialysis of saline water, cation exchange membranes (CEMs) that actively transport Na + and restrict water permeation are required. In this study, we prepared novel CEMs by a heavy-ion-track grafting technique and measured their membrane resistance and water permeation flux as transport properties. The prepared nanostructured CEMs exhibited lower resistance and lower water flux than the commercial CEM. Na + ions were efficiently transported through their unique one-dimensional ion channels (low resistance), while water transport was suppressed due to the very low water uptake of the CEMs. These results demonstrated the high potential of these nanostructured CEMs for use in practical saline water electrodialysis.